A damage-based time-domain wear-out model for wire bond interconnects in power electronic modules - Yang, Li (2013)
In the Physics-of-Failure based approach to reliability design and assessment, which aims to relate lifetime to the identified root-cause of the potential failures, the development of effective failure mechanism models is a crucial task.